Economic evaluation of artificial insemination of sex‐sorted semen on a Brown Swiss dairy farm—A case study. (10th February 2019) - Osada, Masahiro; Iwabuchi, Hitomi; Aoki, Toru; Sasaki, Kika; Ushijima, Hitoshi; Ozawa, Takeyuki
Abstract: Artificial insemination using sex‐sorted semen is employed to efficiently increase the number of female dairy calves born. Previous studies have determined that using sex‐sorted semen is beneficial to improve the management, but the mechanism by which it increases cattle numbers through objective indices of breeding remains unclear. This study focused on a Brown Swiss cattle herd in which frozen female sex‐sorted semen was systematically employed to increase the number of cattle. We analyzed the correlation between the increase in the number of cattle and the screening accuracy of sex‐sorted semen, measuring indices such as pregnancy rate and birth rate of female calves. Study revealed that: (1) production cost for female calves is influenced by the pregnancy rate, rate of female calves, and using sex‐sorted semen is less expensive than using nonsorted semen; (2) improvements in screening accuracy nearly doubled the number of cows and tripled the number of heifers in 5 years; and (3) use of sex‐sorted semen improved milk quality. The pregnancy rate was lower when sex‐sorted semen was used, but the birth rate of heifers was improved. Results suggest that artificial insemination using sex‐sorted semen is beneficial because it economically produces offspring to increase the herd.